The provision of pediatric cardiac anesthesia services in Germany: current status of structural and personnel organization. Issue 8 (17th April 2017) - Baehner, Torsten; Dewald, Oliver; Heinze, Ingo; Mueller, Matthias; Schindler, Ehrenfried; Schirmer, Uwe; Baumgarten, Georg; Hoeft, Andreas; Ellerkmann, Richard K
Summary: Background: Anesthesia for pediatric cardiac surgery requires a high level of expert knowledge. There are currently no recommendations and standards for anesthetic management for congenital cardiac surgery in Germany. Aim: The aim of the present study was to assess the current status of structural and personnel anesthetic standards at pediatric cardiac surgery centers in Germany. Methods: All cardiac surgical centers in Germany were reviewed for an active program for congenital heart surgery. Centers with an active program were invited to respond to an online survey. The questionnaire containing 55 items in 16 categories assessed current practice in pediatric cardiac anesthesia. Results: An active program for pediatric cardiac surgery was identified at 27 centers. The response rate to the survey was 96.3%. A specialized group of anesthesiologists for pediatric cardiac anesthesia was reported from 26 centers (92.3%). The mean size of this group was 4.8 anesthesiologists per center. However, the annual case load of centers and relative annual case load per specialized anesthesiologist varied considerably between 12.5 and 250. Nonanesthesiologists performed sedation and general anesthesia for diagnostic and therapeutic interventions outside the operating theater in children with congenital heart diseases in 24 centers (77%). Although special equipment, for example, pediatric TEE, near‐infrared spectroscopy, and devices for mechanical auto transfusion were available in most centers, their routine use was not always part of standard operating procedures. The proposal for mean adequate training in pediatric cardiac anesthesia as estimated by the participating centers was 10.8 months. Conclusion: The present study represents the current structural situation for anesthesia at German pediatric cardiac surgery centers. Abstract :